2013
DOI: 10.1074/jbc.m113.510065
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Oxidoreductin-1α (Ero1α) Improves Folding and Secretion of Mutant Proinsulin and Limits Mutant Proinsulin-induced Endoplasmic Reticulum Stress

Abstract: Background: Mutant proinsulin-G(B23)V is defective in formation of native disulfide bonds. Results: Overexpression of Ero1␣ partially rescues secretion of mutant proinsulin-G(B23)V. Conclusion: Enhanced ER oxidation is of potential benefit to proinsulin folding. Significance: Diseases involving proinsulin misfolding might be ameliorated by techniques augmenting protein oxidation in the ER of pancreatic ␤-cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 46 publications
2
34
0
Order By: Relevance
“…Increased expression of ER oxidoreductin-1 (Ero1), which helps to catalyze disulfide bond formation in the ER (37), has been found to promote significant escape/rescue of the wild-type proinsulin that is coexpressed with MIDY mutants in the ER (12). Curiously, we also discovered that increased Ero1 expression could directly rescue ER export of a very small fraction of some of the MIDY mutants themselves (14), and this effect has not been adequately explained. To test whether an improvement of proinsulin oxidative folding might account for a small degree of secretory rescue achievable with MIDY mutants, we briefly exposed cells to diamide (1 mmol/L), followed immediately thereafter by diamide washout.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased expression of ER oxidoreductin-1 (Ero1), which helps to catalyze disulfide bond formation in the ER (37), has been found to promote significant escape/rescue of the wild-type proinsulin that is coexpressed with MIDY mutants in the ER (12). Curiously, we also discovered that increased Ero1 expression could directly rescue ER export of a very small fraction of some of the MIDY mutants themselves (14), and this effect has not been adequately explained. To test whether an improvement of proinsulin oxidative folding might account for a small degree of secretory rescue achievable with MIDY mutants, we briefly exposed cells to diamide (1 mmol/L), followed immediately thereafter by diamide washout.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, all MIDY mutations perturb the native disulfide pairing of proinsulin (9,10). The process of proinsulin disulfide bond formation in vivo is complicated by the rapid time scale (<1 min) for proinsulin translation/translocation into the ER lumen (11), the timing of preproinsulin signal peptide cleavage (12), the regulation of the ER lumenal redox environment (13,14), and activity of ER oxidoreductases (15). It is recognized that all three disulfide bonds of insulin, the two “interchain” disulfide bonds called Cys(B7)-Cys(A7) and Cys(B19)-Cys(A20) as well as the intra-A chain disulfide Cys(A6)-Cys(A11)—all of which form within proinsulin—must be intact for optimal insulin bioactivity on the insulin receptor (16).…”
Section: Introductionmentioning
confidence: 99%
“…On a different note, an emerging therapeutic concept is to kill solid tumors by redox attack, which is most prominently illustrated by the preclinical success of photodynamic therapies (Garg and Agostinis, 2014), as well as by the use of PDI inhibitors (Higa et al, 2014;Xu et al, 2014). Finally, defective insulin secretion and ER stress that is caused by folding-impaired genetic variants of proinsulin can be rescued by expression of hyperactive Ero1 (Wright et al, 2013), although increasing Ero1 activity in healthy b-cells predisposes them to developing ER stress and diabetes (Awazawa et al, 2014). Thus, targeted ER hyper-oxidation might be a viable therapeutic strategy in a subset of diabetic syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Mammals have two genes which encode proteins homologous to ERO1a, known as ERO1a and ERO1b [16]. Wright and colleagues [17] have found that ERO1a limits mutant proinsulin-induced ER stress. Modest inhibition of ERO1a promotes signaling in the UPR and precondition cells against severe ER stress [18].…”
Section: Introductionmentioning
confidence: 99%